أثر مسرح العرائس في غرس بعض القيم التربوية لدى الأطفال دراسة ميدانية على تلاميذ الصف الأول بمرحلة التعليم الأساسي (الحلقة الأولى) بمدينة اللاذقية - بشارة, جبرائيل; سلطان, منال أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يعد مسرح العرائس من الوسائل التعليمية التي تحتل اليوم مكانة هامة في ميدان التربية العملية القائمة على التجربة، وتعرف الواقع والممارسة العملية، وهو نشاط فني مدرسي حيث يقبل الأطفال على الدمى بشغف وشوق وتشدهم إلى مسرح الدمى (العرائس) قوى سحرية خفية يمنحوها حبهم ويحاورونها ويناجونها. تتناول الدراسة الحالية أثر مسرح الأطفال (العرائس) في غرس بعض القيم التربوية لديهم, ولتحقيق أهداف البحث تمّ أخذ عينة عشوائية عددها /60/ تلميذاً من تلاميذ الصف الأول بمدينة اللاذقية, وطبق عليهم مقياس تحمل المسؤولية الاجتماعية قبل عرض المسرحية كاختبار قبلي, وبعد عرض المسرحية كاختبار بعدي. وانتهى البحث إلى النتائج الآتية: - وجود فروق بين متوسط درجات الأطفال في الاختبار القبلي ومتوسط درجات الأطفال في الاختبار البعدي في أدائهم لمقياس القيم التربوية, وهذه الفروق لصالح درجات الأطفال في الاختبار البعدي. - وجود فروق بين متوسط درجات الأطفال في الاختبار القبلي ومتوسط درجات الأطفال في الاختبار البعدي في أدائهم لمقاييس (المشاركة والتعاون, آداب السلوك, تحمل المسؤولية, الأمن والسلامة), وهذه الفروق لصالح درجات الأطفال في الاختبار البعدي. The puppets theater is considered one of the educational tools that today occupies an important place in the field of education based on practical experience and know the reality and practice, an activity that a technical school where children accept the dolls with passion and longing and make their sight to its magical powers hidden their love and talk to it. the current study deals with the impact of Children's Theatre (puppets) to instill some of the educational values ​​they have. to achieve the objectives of the research a random sample size of / 60 / student of first-grade students in Lattakia was taken, and applied the social responsibility scale before the play, and after the play test. The answer came in the following results: - There are differences between the average scores of children in pre-testing and the average scores of children in post-test measure in the performance of educational values, and these differences for the scores of children in the post test. - There are differences between the average scores of children in pre-testing and the average scores of children in post-test in the performance of standards (participation and cooperation, ethics, responsibility, security and safety), and these differences for scores of children in the post test.